A new copia-like transposable element found in a Drosophila rDNA gene unit. - Bell, J.R.; Bogardus, A.M.; Schmidt, T.; Pellegrini, M. (Nucleic Acids Research, 1985)
We have discovered a member of a new family of copia-like transposable elements inserted into the non-transcribed spacer between two ribosomal genes (rDNA). This family, which we call 3S18, consists of at least 15 elements which are scattered throughout the Drosophila melanogaster genome. The elements of this family are approximately 6.5 kb long and have 0.5 kb terminal direct repeats. All of the elements appear to have the same restriction sites. The element is mobile as the size pattern of homologous fragments varies among different strains. In situ hybridization results confirm the scattered location and transposable qualities of 3S18. The element is not transcribed into abundant RNA.